Two new adenosine receptor antagonists for the treatment of Parkinson's disease: istradefylline versus tozadenant - Perez Lloret, Santiago (2014)
INTRODUCTION: Adenosine A2A receptors are localized in the brain, mainly within the caudate and putamen nuclei of the basal ganglia. Their activation leads to stimulation of the 'indirect' pathway. Conversely, administration of A2A receptor antagonists leads to inhibition of this pathway, which was translated into reduced hypomotility in several animal models of parkinsonism. AREAS COVERED: In this review, the effects of two A2A receptor antagonists, istradefylline and tozadenant, on parkinsonian symptoms in animal and humans will be discussed. EXPERT OPINION: Animal studies have shown potent antiparkinsonian effects for several A2A receptor antagonists, including istradefylline. In clinical trials, istradefylline reduced OFF time when administered with levodopa, but results are inconclusive. Results with tozadenant are scarce. Modification of thalamic blood flow compatible with reduced inhibition was noted in one small trial, followed by a significant reduction in OFF time in a larger one. Therefore, both drugs show promising efficacy for the reduction of OFF time in levodopa-treated Parkinson's disease patients, but further research is needed in order to obtain definitive conclusions.